A bibliometric analysis of the impact of theoretical frameworks on EU Directives: The case of sustainability reporting and non-financial reporting - Hanna Mysaka; Ivan Derun (Zeszyty Teoretyczne Rachunkowości)
Purpose: The paper aims to demonstrate that the sustainability reporting (SR) theoretical framework dominates over the non-financial reporting (NFR) theoretical frame-work in the transformation of the European Union's (EU) regulatory system of corporate reporting (CR). Methodology/approach: We apply bibliometric analysis and keyword clustering to samples of 88 articles on SR and 14 articles on NFR that were indexed in SCOPUS between 2000 and 2023. Based on these samples, we determine development trends of SR and NFR research domains were the basis for official implementation. Findings: We demonstrate that the SR theoretical framework dominates over the NFR theoretical framework in terms of quantitative and qualitative parameters despite NFR's official status in the EU. Since the NFR theoretical framework was underdevel-oped, it hurt the legal mechanism for reporting practice. The EU's transformation of the regulatory system of CR corresponds to the direction of development of this area in favor of SR. Research limitations/implications: Ignoring the levels of development of SR and NFR theoretical frameworks could lead to the collapse of the official doctrine of NFR in the EU. Originality/value: This study is the first to compare bibliometric characteristics of SR and NFR publications to determine the use of SR and NFR theoretical frameworks for implementing CR in the form of EU Directives.